Empowering Women in Pioneering Oral Health Initiatives for Elderly with Hypertension - Gilang Rasuna Sabdho Wening; Ganendra Anugraha; Jihan Az' Zahra' Medina; Maulida Putri Syarifina; Mayang Aziza Hanif Ardianto; Naqiya Ayunnisa; Nathania Nurani Fripertiwi; Ni Putu Clara Pitaloka (Universitas Airlangga, 2025)
Background: An epidemiology study at Menur Public Health Center revealed that the highest case of hypertension was found in the late elderly (56-65 years) in the period of September-October 2023, most of them have dental and oral problems. Based on data, most elderly (41.82%) don’t seek any treatment when they experience toothache due to limited access and lack of individual awareness. Therefore, an empowerment program of periodic basic oral screening by cadres in Posyandu is needed for early detection to overcome possible obstacles when visiting the dentist experienced by elderly with hypertension. Objectives: To provide training for cadres in Posyandu Werda Asih regarding basic oral screening through the